Training processes throughout teaching performance: a study from the beliefs of university professors - Bailey Moreno, Josefina (2020)
This study aims to know how the training processes of practicing teachers contribute to the construction of beliefs about teaching at the university. Froma qualitative methodology with agrounded theory approach, professors from public and private universities were selected through theoretical sampling. In-depth interviews were conducted to collect data whichwere analytically coded. Among the results it was found that the teachers' beliefs come frominstitutional training of a normative typewhich emphasizes a functional teaching in didactic techniques, use of technology and innovation, excluding training in knowledge of the discipline they teach. Thus,it was also found that teachers carry out self-training processes on a personal initiativefor updating scientific knowledgeand develop their practices teaching with strategies that they themselves use to learn, because they believe in their own learning processes as a valuable source and credible to conduct teaching.